Production of Field Plantable Seedlings of Acacia nilotica in Fifty Days - Kumar, Adarsh; Gupta, R. B. (Indian Forester, 1990)
The studies were conducted to shorten the nursery period of Acacia nilotica for production of field plantable seedlings. Seeds were separately sown in germination box in third week of April and May. Two sizes of polybags viz 28 X 22 cm and 24 X 18 cm were used for raising the seedlings. It has been observed that the seedlings of May sown seeds showed better growth than the April sown seeds. The field plantable seedlings have been produced in about 50 days by the the first week of July by sowing seeds in the third week of May as against about 120 days or more days as per the existing nursery practice. The methodology developed in the present study is economical and time saver.